2012
DOI: 10.1016/j.ygyno.2011.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Keratosis reduces sensitivity of anal cytology in detecting anal intraepithelial neoplasia

Abstract: Objective. To identify factors that may contribute to poor sensitivity of anal cytology in contrast to the sensitivity of anoscopy in heterosexual women. Methods. We analyzed 324 patients with biopsy confirmed diagnosis of genital intraepithelial neoplasia (either vulva, vaginal, or cervical) from 2006 to 2011 who underwent both anal cytology and anoscopy. Cytology, anoscopy, and biopsy results were recorded. Biopsy specimens underwent independent analysis for quality of specimen. Also, biopsy specimens were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…The total number of biopsies was much higher in our study than in any of the previous studies, allowing us to evaluate correlations with features that might influence the performance of anal cytology. The concordance between anal cytology grades and anal histology was poor, as has previously been described [23].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The total number of biopsies was much higher in our study than in any of the previous studies, allowing us to evaluate correlations with features that might influence the performance of anal cytology. The concordance between anal cytology grades and anal histology was poor, as has previously been described [23].…”
Section: Discussionsupporting
confidence: 53%
“…There have been few studies specifically analyzing the performance of anal cytology in comparison with HRA/anal histology in high-risk women. The results have been conflicting, although most studies reported a very low sensitivity [17,23,24], with a small number of anal histological samples for comparison and, in most cases, a low rate of ASIL/AIN diagnosed. Information on features that might influence anal cytology has also been lacking [18].…”
Section: Discussionmentioning
confidence: 99%
“…30 Finally, compared with cervical lesions, anal SIL can be markedly keratinized, which may result in decreased sensitivity for detecting HSIL on cytology. 31 Based on our findings, we suggest that any patient with HSIL cytology should be referred to anoscopy and not use repeat cytology for monitoring disease.…”
Section: Discussionmentioning
confidence: 61%
“…Five of these 12 publications included a small number of HIV+ women, 20,21,40-42 one publication included a cohort of HIV-positive women with IN1-3 (compared with HIV-negative immune compromised and HIV-negative immune competent with IN1-3), 39 and two publications included a comparative cohort of women without a history of IN1-3. 43,44 Two publications included only women from the general population.…”
Section: Resultsmentioning
confidence: 99%